Performar para seguir performando: la cultura fitness - Kogan, Liuba (2005)
The purpose of this paper is to analyze the culture of the body in gymnasiums. It suggests that if these spaces were, before, the redoubt of boxers and of body-builders, who sought to build strong and muscular bodies for physical competition, today they are used to build the post modern performative self. In this way, they propose new technology, practices, norms and knowledges that leave not much space for individual agency. Thus, the body that is attained within the context of the fitness culture is not a metaphor of the machine, or of the conscience’s tool, which requires discipline and training, it isn’t even the mediator of an inner being. The individual who follows the fitness culture is one who performs to keep performing. His fate is constant movement in order to respond constantly and in a flexible way to the changing commands of post-modernity.